2016
DOI: 10.1083/jcb.201601071
|View full text |Cite
|
Sign up to set email alerts
|

Structural, super-resolution microscopy analysis of paraspeckle nuclear body organization

Abstract: Paraspeckles are nuclear bodies built on the long noncoding RNA Neat1. Using structural illumination microscopy, West et al. analyze the organization of paraspeckles at the submicron scale and show that paraspeckle proteins are arranged around bundles of Neat1, forming core-shell spheroidal structures dependent on the RNA binding protein Fus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
368
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 302 publications
(385 citation statements)
references
References 47 publications
14
368
3
Order By: Relevance
“…Indeed, super-resolution microscopy and crosslinking experiments have confirmed that SGs contain a labile liquid shell. These results point to a complex internal organization of SGs, a picture that, given recent work, is likely true for other membraneless organelles as well [24,25,68]. …”
Section: Materials States Of Membraneless Organelles: Liquids Hydrogementioning
confidence: 57%
“…Indeed, super-resolution microscopy and crosslinking experiments have confirmed that SGs contain a labile liquid shell. These results point to a complex internal organization of SGs, a picture that, given recent work, is likely true for other membraneless organelles as well [24,25,68]. …”
Section: Materials States Of Membraneless Organelles: Liquids Hydrogementioning
confidence: 57%
“…For this purpose, the typical shell and core substructures of paraspeckles were visualized by super‐resolution microscopy in HeLa cells (Fig EV2A and B). Specifically, RNA‐FISH was performed with three antisense RNA probes: two corresponding to the 5â€Č and 3â€Č termini of NEAT1_2 , which labeled the shell of the paraspeckle (green signals in Fig EV2A), and one targeting the middle of NEAT1_2 , which labeled the internal area of the paraspeckle (magenta signals in Fig EV2A) (Souquere et al , ; Mito et al , ; West et al , ). All paraspeckles in a cell with an intact shell and core structure were collectively imaged by maximum intensity projection.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 6, Supplementary Material, Figs S2 and S4). Distinct subdomains are observed in several classes of non-neuronal RNA granules, suggesting that common structural strategies underpin the organization of these diverse cytoplasmic assemblages (39)(40)(41)(42).…”
Section: Fxg Structurementioning
confidence: 99%